Limits and possibilities of communication during the Covid-19 pandemic: Mental health experiences (Research, Society and Development, 2024)
The study aims to describe the experiences of professionals at a Child and Youth Psychosocial Care Center (Caps i) during the COVID-19 pandemic regarding communication and to list strategies used by the team in providing care to users and their families. This is a descriptive, qualitative study, based on the five stages of the Problematization Theory through the Maguerez Arch methodology. It addresses the experiences of Caps i professionals during the COVID-19 pandemic concerning the communication process and how the team outlined strategies to continue providing care, albeit in a new format, due to COVID-19. We used three categories: professionals' experiences versus pandemic reality; limits and possibilities in the mental health communication process; and strategies employed to continue the work. The pandemic brought many challenges to mental health. The work was conducted through technological advances, as adaptations were necessary to ensure communication and support for users and families. Despite the uncertainties, the team managed to reinvent itself and, even in the face of the dark times the world went through, implemented changes in the work process within a Caps i.